Antibiotic Use During Pregnancy and Childbirth: Prospective Observational Study on Prevalence, Indications, and Prescribing Patterns in a German Tertiary Center - Schilling, Anna-Lara; Rody, Achim; Bossung, Verena (Geburtshilfe und Frauenheilkunde, 2022)
Introduction Antibiotics are powerful drugs to prevent and treat perinatal infections. Overuse of antibiotics leads to antibiotic resistance, has potential side effects and influences the maternal and neonatal microbiome.Patients and Methods We performed a prospective observational study on the prevalence, indications, and prescribing patterns of antibiotics during pregnancy and childbirth. We included women who had given birth after 23+0 weeks of gestation at a single tertiary center in Germany from January 2020 to March 2021. Descriptive statistics and binomial regression were performed to analyze the factors influencing the prescription of antibiotics.Results We included 522 postpartum women into our study. 337 (64.6%) were exposed to antibiotics during pregnancy and/or childbirth. 115 women received antibiotics during pregnancy, 291 during birth. Most antibiotics during pregnancy were prescribed for urinary tract infections (UTIs) (56.0%). Most prescriptions were issued by obstetrics and gynecology physicians (65.8%), followed by hospitals (16.7%) and family medicine physicians (8.8%). Most antibiotics during childbirth were given for a cesarean section (64.3%), followed by preterm rupture of membranes (41.2%). 95.3% of women who had a preterm birth were exposed to antibiotics. In logistic regression models, lower gestational age at birth, higher maternal body-mass-index and smoking were independently associated with antibiotic use during pregnancy and childbirth.Conclusion We found a high rate of antibiotic exposure during pregnancy and childbirth. Our results imply an urgent need for antibiotic stewardship programs in perinatal medicine as well as further research on the effects of perinatal antibiotic exposure on microbiome development and childhood health.
Keywords: Antibiotika; Schwangerschaft; Antibiotic Stewardship; Mikrobiom